Metode Storytelling dalam Meningkatkan Pemahaman Konsep Geografi di SMA Negeri 3 Tondano - Sagala, Yunita; Kumaat, Joyce Chistian; Rifani, Irfan; Tewal, Selvana Treny Rosita (Jurnal Social Science, 2024)
This study aims to evaluate the effect of applying the Storytelling learning method on students’ conceptual understanding of Population Dynamics material in class XI SMAN 3 Tondano. The research method used is descriptive research with a quantitative approach. During the learning process, students are divided into small groups to discuss the material, and then convey the results of their discussions through stories related to geographic concepts. The results showed that the majority of groups scored high in the aspects of content truth, fluency, intonation, and clarity. The average score was 4 for content truth, fluency, and clarity, and 3 for intonation, which shows that the Storytelling method effectively improves conceptual understanding and speaking skills. In addition, students also showed increased self-confidence and active involvement in the learning process.